2006
DOI: 10.1007/s00405-006-0051-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results and complications following uvulopalatopharyngoplasty in 116 consecutive patients

Abstract: A modified uvulopalatopharyngoplasty (UPPP) was carried out between January 1992 and December 2003 at the ENT Department of the Inselspital in Bern in 146 patients with habitual or complicated rhonchopathy. The operation consisted of a classical tonsillectomy or residual tonsil resection and additional shortening of the uvula. The natural mucosal fold between the uvula and the upper pole of the tonsils was carefully preserved. A wide opening to the rhinopharynx was created by asymmetric suturing of the glossop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
1
Order By: Relevance
“…It has been suggested that altered nasal structure affects olfactory function in OSAS patients [ 13 ]. UPPP improved nasal breathing in many OSAS patients with impaired nasal breathing, so the olfactory function in OSAS patients might be improved by UPPP [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that altered nasal structure affects olfactory function in OSAS patients [ 13 ]. UPPP improved nasal breathing in many OSAS patients with impaired nasal breathing, so the olfactory function in OSAS patients might be improved by UPPP [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A review of the literature on uvulopalatopharyngoplasty, lingual tonsillectomy, and tongue base reduction procedures performed alone did not show evidence of OPS. 4,[10][11][12][13][14][15][16][17][18] Lin and Koltai 19 noted the potential for adhesions between the epiglottis and the tongue base after coblation lingual tonsillectomy and suggested additional caution during ablation of lingual tonsil tissue in the vallecula.…”
Section: Commentmentioning
confidence: 99%
“…Unexpected scar formation and inappropriate selection of patients for surgical treatment may contribute to these poor success rates [1,2]. For these reasons, continuous positive airway pressure (CPAP) therapy is the treatment of choice for OSA.…”
Section: Introductionmentioning
confidence: 99%